Effects of Common Methods of Bracing on pain in Tennis Elbow Disorder - F Jafarian; E Sadeghi (Vesnu Publications, 2008)
Abstract Introduction: many routine activities of patients affected by tennis-elbow disorder is become hampered by pain in lower end of radius. One of the current therapies for this complaint is use of orthosis. Providing prompt function and quick reduction of pain is primary goal of counter-force orthoses.  This study conducted to determine which kind of orthotic treatments relieved pain more efficient in patients suffering from tennis elbow (lateral epicondylitis) disorder. Methods: Fifty individuals diagnosed with lateral epicondylitis by a physician (20 men, 30 women; mean age =41±8 years) having symptoms for at least 3 weeks, were recruited from the community of tennis players The orthosis used were the Counter-Force Tennis Elbow Strap, the Counter-Force Elbow Sleeve, the Wrist Splint and a placebo orthosis that consisted of a modified Patella Strap. Pain is measured with Visual Analogue Scale (VAS) and then analyzed by eleventh version of SPSS software. Independent t-tests and pair t-test were used as statistical tests. Results: No statistically significant differences in pain were observed in wrist splint situations (p>.05), however, counter force strap and sleeve situations, had a rightful effect on pain reduction (p